Integrating Problem-Based Learning into E-Modules : A Development Study with Validation and Student Response Analysis - Linda Safitri; Nurkhairo Hidayati; Suryanti Suryanti (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop an e-module integrated Problem-Based Learning (PBL), validate the feasibility of the developed e-module, and analyze student responses to its use in learning. The research was conducted at two schools in Riau Province, namely SMA Negeri 2 Siak Hulu and SMA Negeri 3 Siak Hulu, employing the ADDIE development model, which was focused up to the development stage. Validation was carried out by five experts consisting of subject matter, media, and instructional experts. The instruments employed in this study were a validation sheet and a student response questionnaire. Data analysis was conducted by calculating the results of the validation test and the students' responses. The validation results indicated a very high level of validity, with an average score of 97% from media experts, 97% from subject matter experts, and 98% from instructional experts. Furthermore, the student response to the e-module usage yielded an average score of 94%, categorized as very good. This e-module was specifically designed for the cell topic in biology, featuring an interactive interface accessible both offline and online. The integration of the PBL model into the e-module was implemented through stages of problem orientation, learning organization, investigation, product development, and analysis and evaluation. Therefore, this study recommends the use of the e-module integrated PBL as an innovative alternative teaching material to improve student learning outcomes and serve as a reference for technology-based instructional material developers.